Multiple Mixing Ratios of Gamma Rays From Reaction Using a2-ratio Method - Youhana, H.M.; Saied, B.M.; Younis, T.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The -multiple mixing ratios of Î³-transitions from levels of populated in the are calculated in the present work by using the a2-ratio methods. We used the experimental coefficient (a2) for two Î³ -transitions from the same initial state, the statistical tensor, which is related to the a2-coefficient would be the same for the two transitions. This method was used in a previous work for pure transitions or which can be considered pure. In these cases the multiple mixing ratios for the second transition ( ) equal zero, but in our work we applied this method for mixed Î³-transitions and then the multiple mixing ratio ( ) is known for one transition. Then we calculate the ( ) value and versareversa. The weight average of the -values calculated in the present work for a mixed transition in are presented as adopted -value. The result obtained confirms the valibites of this method to calculate the multiple mixing ratios ( ) for Î³-transitions and their capabilities in predicting any inaccuracies in the experimental data.